Corn Ribs : Inovasi Olahan Jagung untuk Pemberdayaan UMKM Desa Bah Joga Kecamatan Jawa Maraja Bah Jambi Kabupaten Simalungun - Nova Apriani Purba; Siti Endang Sariniah; Nesya Aulia; Yulinda Yulinda; Franindya Purwaningtyas (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2026)
Corn is one of the potential agricultural commodities in Bah Joga Village however, its utilization has mostly been limited to traditional products, resulting in relatively low economic value. This study aims to introduce corn ribs as an innovative food product derived from local corn, which is expected to strengthen the empowerment of micro, small, and medium enterprises (MSMEs) in the village. A descriptive qualitative approach was employed through observation, interviews, and literature review related to food innovation and small business development. The findings indicate that corn ribs have promising market potential since they combine flavors that suit modern consumer preferences with raw materials that are easily accessible locally. Furthermore, processing corn into corn ribs can increase the selling value of agricultural products, open new business opportunities, and enhance the competitiveness of local MSMEs. Therefore, this innovation not only contributes to the diversification of food products but also supports the economic improvement of Bah Joga Village through the development of creative enterprises based on local resources.